Fassbinder's germany: history identity subject - Elsaesser, Thomas (Film Culture in Transition, 1996)
Rainer Werner Fassbinder is one of the most prominent and important authors of post-war European cinema. Thomas Elsaesser is the first to write a thoroughly analytical study of his work. He stresses the importance of a closer understanding of Fassbinder's career through a re-reading of his films as textual entities. Approaching the work from different thematic and analytical perspectives, Elsaesser offers both an overview and a number of detailed readings of crucial films, while also providing a European context for Fassbinder's own coming to terms with fascism.